(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The banking sector is core competency of the worldeconomy which influences the strength of every nation’s economy in the worldeconomy. The overall development and growth of any economy depends more on thesound services sector. The role of service sector in Indian economicdevelopment has increased by several notches from the fact that service sectorwhich was contributing only 20 percent during the independence time, now it iscontributing over 50 pc of GDP India. Indian economy is the fastest growingmajor economy in the world with GDP growth rate of 8.4 percent at the end ofthird quarter of 2007-08.